Challenges in the articulation between the national Philosophy curriculum, Secondary Education and university training in Philosophy Pedagogy in Chile (Olhar de Professor, 2025)
This article explores the curricular alignment among the national philosophy curriculum, teaching practices in schools and universities, and pedagogical training specifically in philosophy. Using qualitative research, which involved analyzing two focus groups and thoroughly reviewing eleven curricular documents, the study identifies a positive convergence between educational programs and transversal learning objectives. This indicates a substantial effort to integrate philosophical education as a core component in students' comprehensive development. Despite these advances, several areas require further attention, suggesting that current curricular articulation -though valuable- still contains gaps that could be addressed through targeted strategies to foster research skills and critical dialogue and to strengthen coherence between the school curriculum and university teacher education. The findings highlight the importance of strengthening curricular alignment to enhance both philosophy teaching and its contribution to students' holistic development. Additionally, the study emphasizes implementing effective pedagogical practices that foster critical thinking, research skills, and a stronger connection between theoretical knowledge and educational practice.
Keywords: Curricular articulation; Teaching of Philosophy; National curriculum; Teacher planning; Philosophy teacher training